Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kompetensi Guru Sekolah Menengah Atas Negeri 2 Kotabaru - Farihatun -; Ida Marwan (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2010)
Leadership is an important strength for the agenda of management. On that account, ability leads effectively is locking success of organization. Existence of leader implementing function of its(the leadership in facing changes happened in school by specifying purpose of in intact ( firm and purposeful, exploits subordinate through partisipative approach ( a participate approach), and constituted by leadership ability professionally ( the leading professional) becomes leadership indicator of effective school. There are three element in leadership, that is: firstly, every leadership must entangle others or subordinate. Second, leadership always related to power along with distribution of its(the power. Third, leadership coping inculcates influence to others or. follower to motivat to work. Therefore, headmaster as leader of having to be able: Generates strong willingness vigorously and self confidence of the subordinates in executing each duty. Gives tuition and guidance to the subordinates and gives motivation, races and stands up in front of for the shake of progress and gives inspiration in reaching purpose.